Report on vocational education and training for the year 2009 - (:unkn) unknown (My University, 2009)
This Report on Vocational Education and Training is the first one published in a new and more "slim" format. "Former part I (the 'political part') will focus on the statutory terms of reference and provide an overview of important VET policy decisions, developments and measures. It will be submitted to the German Parliament (Deutscher Bundestag) as a stocktaking exercise and a report by the Federal Government on vocational education and training. From 2009 onwards, former part II will be published separately and in a new format as a 'Data Report' annexed to the 'Report on Vocational Education and Training', providing a host of information, charts and analyses covering the development of VET in Germany and in the European context. The Data Report will be published by the Federal Institute for Vocational Education and Training (Bundesinstitut für Berufsbildung - BIBB) as a major complement to the Federal Government's Report, especially in terms of statistics." (Editor, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 3.5.1.1 Bundesministerium für Bildung und Forschung (BMBF); S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); G 1.3.1.1 Ausbildungsstellenmarkt; S 2.3.2 Programme in der Berufsbildung; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 1 Internationale Berufsbildung; P 1.7 Benachteiligte; Berufsbildungsbericht; Berufsbildungspolitik; Duales System; Ausbildungsplatzförderung; Ausbildungsstellenmarkt; Benachteiligtenförderung; Übergangssystem; Durchlässigkeit im Bildungssystem; Beschäftigungsfähigkeit; Lebenslanges Lernen; Internationale Zusammenarbeit; 2009